Analisis Kontrol Kualitas Produk Ikan Dori Di PT.Aerofood Indonesia Unit Surabaya - Viandini, Alfian Pramesthi Dwi; Sri Handajani; Ila Huda Puspita Dewi; Lilis Sulandari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Quality control is a process to ensure that the products or services produced meet the standards or specifications that have been set. Dori fish (Zeus Faber) is a perishable food, so it requires proper handling and processing to maintain its quality. This study aims to determine the quality control of flour fried dori fish products at PT. Aerofood Indonesia Surabaya unit which includes the preparation, processing and storage stages with qualitative descriptive research methods through observation and interviews conducted with 5 resource persons. The results of the study show that 1). The preparation stage includes equipment, thawing, and cutting 100% meets the standard, marinade reaches 60% meets the standard, the marinade is evenly distributed 80% according to the standard and for the batter dough 60% according to the standard. 2). The processing stage of frying temperature control reaches 80% according to the standard, the number of frying in large quantities and the color of the product maturity is 100% according to the standard, the blast chiller is 100% meets the standard. 3) The final storage stage of the product including portioning and final storage is 100% compliant with the standard.